2017
DOI: 10.1093/jpids/pix065
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Dental Clinic–Associated Outbreak of Mycobacterium abscessus Infection

Abstract: M abscessus infection was associated with significant medical morbidity and treatment complications. Unique manifestations included extranodal mandibular or maxillary osteomyelitis and pulmonary nodules. Challenges in the identification of case-children resulted from an extended incubation period and various clinical manifestations. Clinicians should consider the association between M abscessus infection and pulpotomy in children who present with subacute cervical lymphadenitis. The use of treated/sterile wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Two immunocompromised patients have presented a dental abscess associated with Pseudomonas aeruginosa after exposure to DUWL water contaminated by this microorganism [6]. Groups of children developed infections with Mycobacterium abscessus after having pulpotomy in a hospital in which DUWL were contaminated by this nontuberculous mycobacterium [7,8]. Infectious risk can also affect the healthcare workers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Two immunocompromised patients have presented a dental abscess associated with Pseudomonas aeruginosa after exposure to DUWL water contaminated by this microorganism [6]. Groups of children developed infections with Mycobacterium abscessus after having pulpotomy in a hospital in which DUWL were contaminated by this nontuberculous mycobacterium [7,8]. Infectious risk can also affect the healthcare workers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of NTM in the water should also be monitored after disinfection of the waterlines as the use of a low-level disinfectant will remove most bacteria but can lead to an accumulation of NTM. In Caracas, Venezuela, and also in the USA, outbreaks of NTM infections have been registered as being associated with NTM-contaminated water in DUWLs [14][15][16]. In order to keep patients safe, one must use water of an appropriate microbiological quality or sterile water, especially when surgical procedures are performed and/or when treating certain groups of people, e.g., immunocompromised and older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our research shows that they can be isolated and identified from water in DUWLs. Moreover, outbreaks due to these bacteria after odontological care have recently been reported I the USA and in Venezuela [14][15][16].…”
Section: Nontuberculous Mycobacteria In Duwlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenitis was the principal clinical feature of an outbreak of odontogenic M. abscessus infections involving 24 children, who underwent pulpotomy at a single dental practice in Georgia between October 2013 and September 2015. 120 Pulpotomy is not considered to be a surgical procedure and consequently, municipal water is often used during drilling and irrigation. Water samples from the dental chairs were contaminated with M. abscessus in quantities that exceeded the Environmental Protection Agency's microbiologic cutoff safety standard for drinking water by 180-fold.…”
Section: Cervicofacial Adenitismentioning
confidence: 99%